Exploring Malay-Islamic ethnomathematics: al-Khatib's combinatoric theory in 'Alam Al-Hussab and Raudah Al-Hussab - Ismail, Mat Rofa; Ismail, Habsah (Elsevier, 2010)
In this paper, we take the position of exploring ethno-mathematics, a branch of knowledge on mathematical thinking of a certain ethnic group on the mathematical concept of permutation and combination, in malay world under the islamic influence. The subject mathematics was taught and studied in the malay region in conjunction with other branches of knowledge especially the ones that are related to islamic jurisprudence before the arrival of western mathematics. With reference to two classical texts of the same author of the late 19th century as evident in the title of this article, quantitative and qualitative aspects of etnomathematics, characterised by their values and thinking of the subject were discussed.